KEEFEKTIFAN MEDIA SPOTLIGHT BOOK DENGAN MODEL SAVI TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN IPS - Khoerunnisa, Sofiana (Universitas Pendidikan Ganesha, 2018)
This research aimed to identify and analyze the effectiveness of spotlight book media with SAVI model towards the critical thinking skill of students on IPS studies, 4th Grade of SD N Wangandalem 01 Brebes. This research was a quantitative research with research design that was Pre Experimental Design in the form of One Group Pretest-Posttest Design. The variable that used by researcher is dependent variable (attached) that was the critical thinking skill of students and independent variable (free) that was spotlight book media with SAVI model. The data collection of this research was giving 10 questions of critical thinking skill of students on pre-test and post test, for getting the different result of critical thinking skill of students between before and after doing that. For applying spotlight book media with SAVI model was obtained the enhancement result of average value of studentsâ critical thinking skill as much as 15.27% from 63.92 to 79.19. Keywords: Critical thinking skill, Spotlight Book, SAVI